Pretreatment cognitive deficits and treatment effects on attention in childhood absence epilepsy - Masur, David; Shinnar, Shlomo; Cnaan, Avital; Shinnar, Ruth C; Clark, Peggy; Wang, Jichuan; Weiss, Erica F; Hirtz, Deborah G; Glauser, Tracy A (Neurology, 2013)
To determine the neurocognitive deficits associated with newly diagnosed untreated childhood absence epilepsy (CAE), develop a model describing the factorial structure of items measuring academic achievement and 3 neuropsychological constructs, and determine short-term differential neuropsychological effects on attention among ethosuximide, valproic acid, and lamotrigine. Subjects with newly diagnosed CAE entering a double-blind, randomized controlled clinical trial had neuropsychological testing including assessments of general intellectual functioning, attention, memory, executive function, and achievement. Attention was reassessed at the week 16-20 visit. At study entry, 36% of the cohort exhibited attention deficits despite otherwise intact neurocognitive functioning. Structural equation modeling of baseline neuropsychological data revealed a direct sequential effect among attention, memory, executive function, and academic achievement. At the week 16-20 visit, attention deficits persisted even if seizure freedom was attained. More subjects receiving valproic acid (49%) had attention deficits than subjects receiving ethosuximide (32%) or lamotrigine (24%) (p = 0.0006). Parental assessment did not reliably detect attention deficits before or after treatment (p < 0.0001). Children with CAE have a high rate of pretreatment attentional deficits that persist despite seizure freedom. Rates are disproportionately higher for valproic acid treatment compared with ethosuximide or lamotrigine. Parents do not recognize these attentional deficits. These deficits present a threat to academic achievement. Vigilant cognitive and behavioral assessment of these children is warranted. This study provides Class I evidence that valproic acid is associated with more significant attentional dysfunction than ethosuximide or lamotrigine in children with newly diagnosed CAE.